Green business models in the construction sector: an analysis of outcomes and benefits. Issue 1 (2nd January 2018) - Abuzeinab, Amal; Arif, Mohammed; Qadri, Mohd. Asim; Kulonda, Dennis
Abstract : Purpose: Green business models (GBMs) in the construction sector represent the logic of green value creation and capture. Hence, the call to examine GBMs is growing ever louder. The aim of this paper is to identify benefits of GBMs by adopting five essential elements of the GBM from the literature: green value proposition; target group; key activities; key resources (KR); and financial logic. Design/methodology/approach: In all, 19 semi-structured interviews are conducted with construction sector practitioners and academics in the UK. Thematic analysis is used to obtain benefits of GBMs. Further, the interpretive ranking process (IRP) is used to examine which elements of the GBM have a dominant role in providing benefits to construction businesses. Findings: The benefits are grouped into three themes: credibility/reputation benefits; financial benefits; and long-term viability benefits. The IRP model shows that the element of KR is the most important when evaluated against these three benefit themes. Practical implications: Linking GBM elements and benefits will help companies in the construction sector to analyse the business case of embracing environmental sustainability. Originality/value: This research is one of the few empirical academic works investigating the benefits of GBMs in the construction sector. The IRP method is a novel contribution to GBMs and construction research.